Dual functional MoS2/graphene interlayer as an efficient polysulfide barrier for advanced lithium-sulfur batteries. (1st December 2017) - Guo, Pengqian; Liu, Dequan; Liu, Zhengjiao; Shang, Xiaonan; Liu, Qiming; He, Deyan
Highlights: Dual functional MoS2 /graphene interlayer was first used as an efficient polysulfide-trapping shield for lithium-sulfur batteries. MoS2 /graphene interlayer shows strong chemical interactions with LiPSs. MoS2 /graphene interlayer forms a 3D network to facilitate electron and ion transfer during the discharge-charge processes. The resultant lithium-sulfur batteries exhibit a superior rate capacity and improved cycling capacity. Abstract: A dual functional interlayer consisted of composited two-dimensional MoS2 and graphene has been developed as an efficient polysulfide barrier for lithium-sulfur batteries (LSBs). With such a configuration, LSBs show a superior rate capacity and improved cycling capacity. The excellent electrochemical performance can be attributed to the strong bonding interactions between the MoS2 /graphene interlayer and the formed lithium polysulfides (LiPSs) as well as the good electrical conductivity of the MoS2 /graphene composite. The MoS2 /graphene interlayer can physically block LiPSs by the graphene nanosheets and chemically suppress the dissolution of LiPSs by the polar MoS2 nanoflowers. Such a dual functional interlayer further provides a good contact with the surface of the sulfur cathode, acts as an upper current collector and greatly improves the sulfur utilization and the rate capability of LSBs.